Effect of Virtual Collaborative Learning with Mobile Devices on Patient Safety Culture among the Staff of a Maternity Center - Soheila Nooriani; sonia Oveisi; Ahad Alizadeh; Forouzan Olfati (Golestan University of Medical Sciences, 2022)
Background: Improving patient safety is a common international priority because errors and other forms of unnecessary damage to the process of patient care and treatment are global problems. Training programs such as web-based programs enhance the patient safety culture in staff. This study was carried out to evaluate the impact of virtual collaborative learning with mobile devices on patient safety culture among the staff of a maternity center. Methods: This study was conducted on staff working in Kowsar Hospital of Qazvin in 2019 with a pretest-posttest design. Sixty-three eligible participants were recruited using convenience sampling. The educational contents were shared on a website. Data were collected online using the hospital Survey on Patient Safety Culture questionnaire. Educational intervention sessions were held once a week, for 8 weeks. The paired t-test and chi-square test were used for statistical analysis. The significance level was set at 0.05. Results: The mean score of safety culture increased significantly from 141.19±16 to 147.93±14.05 after the intervention (P<0.001). Error reporting at the center also increased significantly after the intervention (P<0.001). Conclusion: This research showed that the collaborative method using mobile learning can be effective for the promotion of patient safety culture among the maternity center staff.